2012
DOI: 10.1159/000338629
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intraoperative Amino Acid Infusion on Blood Glucose under General Anesthesia Combined with Epidural Block

Abstract: Aim: To investigate the effect of intraoperative amino acid infusion on blood glucose in patients under general anesthesia combined with epidural block. Methods: 36 patients were randomly assigned to receive an intraoperative infusion of 18 compound amino acids (group AA) or lactated Ringer solution (group LR) at 2 ml·kg–1·h–1. Nasopharyngeal temperature, and blood glucose, plasma insulin, C-peptide and glucagon concentrations were measured 30 min before induction (T0), 10 min after induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…It is suggested that intraoperative amino acid infusion is beneficial to maintain normal perioperative temperature in patients undergoing gastrointestinal surgery without increasing the risk of hyperglycemia or causing damage to liver and kidney function. It is safe to prevent perioperative hypothermia (15). In 2008, amino acid was also reported in related applications in OPCAB (16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is suggested that intraoperative amino acid infusion is beneficial to maintain normal perioperative temperature in patients undergoing gastrointestinal surgery without increasing the risk of hyperglycemia or causing damage to liver and kidney function. It is safe to prevent perioperative hypothermia (15). In 2008, amino acid was also reported in related applications in OPCAB (16).…”
Section: Discussionmentioning
confidence: 99%
“…Intraoperative infusion of amino acid injection is also one of the most popular perioperative insulation measures in recent years (14)(15)(16). Some studies have proved the effectiveness and safety.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, the postoperative blood glucose values were increased in the control group (from 5.21 mmol/l to 5.77 mmol / l), while in the study group were decreased (from 5.39 mmol / l to 4.79 mmol/l). Maitra et al [20], Zong et al [21] and Srceva et al [22] argue that the administration of different fluids in the pre-operative period differently affect the blood sugar levels. From this study and the studies of Srceva [22] and Zong [21] we can clearly conclude that pre-operatively given amino acids has strong positive impact on the postoperative blood glucose levels.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study of patients undergoing surgery under general anesthesia combined with epidural block, the thermogenic effects of intraoperative AAs infusion were not significant in the early part of surgery; they were most obvious at 2 h after the induction of anesthesia [ 14 ]. This was consistent with our results.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies [ 10 ], the standard deviation of body temperature was approximately 0.1–0.2 °C, and the expected difference between groups was approximately 0.3–0.5 °C; therefore, less than nine patients in each group were calculated to be sufficient for this outcome (power 80 %, α = 0.05). On the basis of an expected difference in blood glucose concentration of 1 mmol·L −1 between the two groups (standard deviation =1 mmol·L −1 ; power 80 %, α = 0.05), 17 patients in each group were calculated to be sufficient for this study [ 10 , 13 , 14 ]. Thus, 20 patients in each group were deemed sufficient for this study.…”
Section: Methodsmentioning
confidence: 99%